THE METHODS OF USING SPECIAL EXERCISES IN DEVELOPING TACTICAL ACTIONS OF YOUNG FOOTBALL PLAYERS - Bori Nigmanov (Modern American Journals, 2025)
This article examines the application of special exercises aimed at developing tactical actions among young football players. The focus is placed on the importance of integrating tactical thinking into early stages of football training and the ways in which specific exercises can foster decision-making, positional awareness, and team coordination. The research highlights various methods of organizing practice sessions that simulate match-like scenarios, thereby preparing youth players for real-game situations. Moreover, the study outlines the pedagogical approaches and principles behind the selection and implementation of tactical drills, based on age-specific characteristics and cognitive development of young athletes. The results of the analysis suggest that structured tactical training significantly enhances the competitive performance and game intelligence of football players in formative years.
Keywords: Football, youth players, tactical development, special exercises, training methodology, decision-making, sports education.